Profiling Self-regulated Learning in Online Mathematics Teacher Training: A Case Study of a GeoGebra Course - Marfuah Marfuah (Southeast Asian Mathematics Education Journal, 2017)
Online training has now become an alternative means of delivering continuousprofessional development courses to improve teacher competencies. The benefits of online training are flexibility of access, cost efficiencies, ease of content updates, and uniformity of content. However, there are many aspects that determine if teachers can be successful in online training, and one is self-regulated learning. This study aims to profile self-regulated learning as case study in an online mathematics teacher training held by PPPPTK Matematika using GeoGebra. Using a survey method, this study describes the participants’ self-regulated learning profile as they accomplished nine tasks in the GeoGebra course.